A walk along the Antonine Wall in 1825: the travel journal of the Rev John Skinner - Keppie, Lawrence (Proceedings of the Society of Antiquaries of Scotland, 2004)
In 1825 the Rev John Skinner, an Anglican clergyman from Camerton in Somerset, walked the length of the Antonine Wall from east to west, as part of an extensive Scottish tour. He recorded his observations at length in a journal and prepared daily a series of pencil sketches which constitute an invaluable record of the monument at a fixed date. His sketches include sculptures and inscriptions subsequently lost, and a few sites otherwise unrecorded. He also visited the Hunterian Museum in Glasgow in order to view its collection of Roman stones.